2012
DOI: 10.3201/eid1810.111929
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Outbreaks in High-Income Area, Kaohsiung City, Taiwan, 2003–2009

Abstract: Cases distribute in a clustered pattern, and elderly persons have the highest risk for illness and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 27 publications
3
34
2
Order By: Relevance
“…In our study this did not result in increased mortality unlike in Puerto Rico [17] and Taiwan [7], [18]. The reasons for this are unclear as the elderly cohort suffered more severe disease.…”
Section: Discussioncontrasting
confidence: 51%
“…In our study this did not result in increased mortality unlike in Puerto Rico [17] and Taiwan [7], [18]. The reasons for this are unclear as the elderly cohort suffered more severe disease.…”
Section: Discussioncontrasting
confidence: 51%
“…Dengue fever is an acute mosquito-borne viral infection caused by the dengue virus (DENV) that imposes considerable morbidity globally, particularly in the tropics and subtropics [ 1 3 ]. DENV is transmitted by several mosquito species within the genus Aedes , principally A .…”
Section: Introductionmentioning
confidence: 99%
“…The Aedes aegypti mosquitoes are predominant in southern Taiwan and highly correlated with dengue epidemics or outbreaks. 2 Previous reports have indicated that dengue epidemics or outbreaks have mainly occurred in the south of Taiwan, such as Tainan and Kaohsiung, 3 which are neighboring cities. Dengue activity has mainly been found in Kaohsiung city.…”
mentioning
confidence: 99%
“…Dengue activity has mainly been found in Kaohsiung city. 3 The co-circulation of two or even four dengue serotypes (DENV-1–4) has been reported in Kaohsiung city. 4 …”
mentioning
confidence: 99%